An analysis of variations in public health nursing referral management and its application to workload measurement. - Wilson, Verna Lillian. (University of Ottawa (Canada), 1990)
The study was designed to answer questions about the amount of professional time required to manage the referrals made to the Ottawa-Carleton Health Department for public health nursing service to individuals and families. The basic assumption of the study was that variation in referral management time would be shown to be the product of both client-centred and provider-centred factors. The study design was both descriptive and exploratory in nature. The study population consisted of 1143 clients referred for public health nursing service during the latter months of 1987. To collect the necessary information, a data collection system was devised in which public health nurses recorded the amount of time they spent providing service for each new case. Based on the study results, modifications were proposed to the weighting system which had been used to predict the referral management component of the public health nursing workload. (Abstract shortened by UMI.)
Keywords: Health Sciences, Nursing.